Introduction to Accounting: Financial Statements (Part One of Accounting Fundamentals in Plain Language) (Book). - Zen, Stephen A. (The Accounting Review, 1965)
Reviews the book "Introduction to Accounting: Financial Statements," by Joseph H. Boyland.